2017
DOI: 10.1186/s13058-017-0860-3
|View full text |Cite
|
Sign up to set email alerts
|

Tightly controlled MRTF-A activity regulates epithelial differentiation during formation of mammary acini

Abstract: BackgroundMyocardin-related transcription factors (MRTF) A and B link actin dynamics and mechanotransduction to gene expression. In mice, MRTF-A is involved in mammary gland differentiation, but its role in human mammary epithelial cells remains unclear.MethodsThree-dimensional cultures of human mammary epithelial MCF10A cells were used to model acinar morphogenesis. Stable MRTF-A knockdown, MRTF-A/B rescue and MRTF-A/B overexpression was established to characterize the functional role during morphogenesis usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
29
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(35 citation statements)
references
References 45 publications
6
29
0
Order By: Relevance
“…In line with our present data for primary endothelial cells, Cui et al have reported that MRTF-A translocates much faster than YAP when fibroblasts are subjected to cyclic stretching forces (Cui et al, 2015). More recently, a study from the Posern group has highlighted that a precise temporal control of MRTF-A is required for the formation of mammary acini (Seifert and Posern, 2017).…”
Section: Discussionsupporting
confidence: 91%
“…In line with our present data for primary endothelial cells, Cui et al have reported that MRTF-A translocates much faster than YAP when fibroblasts are subjected to cyclic stretching forces (Cui et al, 2015). More recently, a study from the Posern group has highlighted that a precise temporal control of MRTF-A is required for the formation of mammary acini (Seifert and Posern, 2017).…”
Section: Discussionsupporting
confidence: 91%
“…The role of matrix stiffness on control of MRTF activation appears to be essential in promoting contact‐mediated proliferation and metastasis. Forced overexpression of MRTF overcomes the requirement of stiffness‐mediated G‐actin recruitment and leads to protection from anoikis in mammary epithelial cells, regardless of matrix stiffness, implying that mechanical cues strictly regulate MRTF activation, not endogenous MRTF signaling functions 199. Further, mouse models of peritoneal fibrosis have shown that lysophosphatidic acid (LPA) signaling at sites of tissue injury induces MRTF nuclear activation and upregulation of connective tissue growth factor (CTGF) expression in mesothelial cells 200.…”
Section: Signaling Through the Cytoplasmmentioning
confidence: 99%
“…Proper function of the mechanically sensitive proliferation pathway is required for regulating the proliferation requirements of anchorage‐dependence and contact‐inhibition. Upregulated activation or expression of FAK, ERK pathway members, and/or the Rho‐actin‐MRTF axis are responsible for loss of proliferation control mechanisms that underly pathological hyperproliferation 199,201…”
Section: Signaling Through the Cytoplasmmentioning
confidence: 99%
“…EMT and its opposite MET (mesenchymal-to-epithelial transition) are significantly involved in stemness balance in both normal and malignant cell spheroids, and their modulation is strategic for the achievement of specific cell phenotypes [ 3 , 4 , 5 , 6 ]. At molecular level, EMT is mediated by the activation of several transcription factors (TFs), including those belonging to the Snail superfamily, such as SNAI1 and SNAI2 [ 7 ], by the loss of cell-junction molecules, such as E-cadherin (encoded by CDH1 ), and the acquisition of mesenchymal markers, such as vimentin.…”
Section: Introductionmentioning
confidence: 99%